Answer: x= -4
Explanation:
3x + -4 = 7x + 12
Reorder the terms:
-4 + 3x = 7x + 12
Reorder the terms:
-4 + 3x = 12 + 7x
Solving
-4 + 3x = 12 + 7x
Solving for variable 'x'.
Move all terms containing x to the left... all other terms to the right.
Add '-7x' to each side of the equation.
-4 + 3x + -7x = 12 + 7x + -7x
Combine like terms: 3x + -7x = -4x
-4 + -4x = 12 + 7x + -7x
Combine like terms: 7x + -7x = 0
-4 + -4x = 12 + 0
-4 + -4x = 12
Add '4' to each side of the equation.
-4 + 4 + -4x = 12 + 4
Combine like terms: -4 + 4 = 0
0 + -4x = 12 + 4
-4x = 12 + 4
Combine like terms: 12 + 4 = 16
-4x = 16
Divide each side by '-4'.
x = -4
Simplifying
x = -4